A Report on Molecular Detection and Phylogenetic Evaluation of Anaplasma marginale in Ticks and Blood Samples Collected from Cattle in District Layyah in Punjab (Pakistan) - Ashraf, Sehrish; Parveen, Asia; Muhammad Awais, Mian; Gillani, Quratulane; Aktas, Munir; Ozubek, Sezayi; Iqbal, Furhan (Springer, 2021)
Anaplasmosis is a tick-borne disease caused by obligate intercellular gram-negative bacteria, Anaplasma (A.) marginale. The present study reports on seasonal prevalence, epidemiology, and phylogeny of A. marginale in three cattle breeds from District Layyah, Southern Punjab, Pakistan. A total of 844 blood samples (Cross = 300, Holstein Friesian = 244, Sahiwal breed = 300) from apparently healthy cattle on seasonal basis were collected along with epidemiological data during May 2018 till April 2019. Polymerase chain reaction generated 265 base-pair amplicon specific for major surface protein-1b encoding gene of A. marginale in 8.6% (73/844) of enrolled cattle. The highest prevalence was observed during autumn (18.3%) followed by summer (9.7%) and winter season (7.1%). Holstein Friesian breed was most susceptible to A. marginale infection (13.1%) followed by Sahiwal (7.6%) and cross breed (6%). Representative amplified partial gene sequences of A. marginale were submitted to GenBank (Accession numbers MK032842 and MK032843). 37/844 (4.3%) Giemsa-stained blood smears were found positive for Anaplasma spp. Small number of ticks including Hyalomma anatolicum, Hyalomma excavatum, Rhipicephalus microplus, Haemaphysalis punctata were identified from cattle but none of them was found PCR positive for the presence of A. marginale. Analysis of epidemiological factors revealed that female cattle and farm with water supply from pool, farms where other dairy animals and dogs were living with cattle and dogs having ticks load on them had significant association with A. marginale prevalence. It was observed that white blood cell, lymphocytes (%), monocytes (%) hematocrit, mean corpuscular hemoglobin, and mean corpuscular hemoglobin concentration were significantly disturbed in A. marginale-positive than negative cattle.
Keywords: Acari Ixodidae; Risk-Factors; Prevalence; Buffalos; Bovis